BM-1197: A Novel and Specific Bcl-2/Bcl-xL Inhibitor Inducing Complete and Long-Lasting Tumor Regression In Vivo - Bai, Longchuan; Chen, Jianfang; McEachern, Donna; Liu, Liu; Zhou, Haibin; Aguilar, Angelo; Wang, Shaomeng (PLOS ONE, 2014)
Bcl-2 and Bcl-xL are critical regulators of apoptosis that are overexpressed in a variety of human cancers and pharmacological inhibition of Bcl-2 and Bcl-xL represents a promising strategy for cancer treatment. Using a structure-based design approach, we have designed BM-1197 as a potent and efficacious dual inhibitor of Bcl-2 and Bcl-xL. BM-1197 binds to Bcl-2 and Bcl-xL proteins with Ki values less than 1 nM and shows >1,000-fold selectivity over Mcl-1. Mechanistic studies performed in the Mcl-1 knockout mouse embryonic fibroblast (MEF) cells revealed that BM-1197 potently disassociates the heterodimeric interactions between anti-apoptotic and pro-apoptotic Bcl-2 family proteins, concomitant with conformational changes in Bax protein, loss of mitochondrial membrane potential and subsequent cytochrome c release to the cytosol, leading to activation of the caspase cascade and apoptosis. BM-1197 exerts potent growth-inhibitory activity in 7 of 12 small cell lung cancer cell lines tested and induces mechanism-based apoptotic cell death. When intravenously administered at daily or weekly in H146 and H1963 small-cell lung cancer xenograft models, it achieves complete and long-term tumor regression. Consistent with its targeting of Bcl-xL, BM-1197 causes transit platelet reduction in mice. Collectively, our data indicate that BM-1197 is a promising dual Bcl-2/Bcl-xL inhibitor which warrants further investigation as a new anticancer drug.